2019
DOI: 10.1002/mds.27728
|View full text |Cite
|
Sign up to set email alerts
|

Parafoveal thinning of inner retina is associated with visual dysfunction in Lewy body diseases

Abstract: Background Retinal optical coherence tomography findings in Lewy body diseases and their implications for visual outcomes remain controversial. We investigated whether region‐specific thickness analysis of retinal layers could improve the detection of macular atrophy and unravel its association with visual disability in Parkinson's disease. Methods Patients with idiopathic Parkinson's disease (n = 63), dementia with Lewy bodies (n = 8), and E46K mutation carriers in the α‐synuclein gene (E46K‐SNCA) (n = 4) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 51 publications
5
45
0
Order By: Relevance
“…More recent publications have shown that the thinning of macular GCIPL in PD is linked to cognitive impairment in de novo patients 23 and to the risk of dementia 18 . Interestingly, our group found that visual dysfunction in PD is selectively associated with the thinning of GCIPL in the 1‐ to 3‐mm diameter ring area around the fovea (parafoveal GCIPL), 20 an OCT feature that has also been identified in patients with idiopathic rapid eye movement sleep behavior disorder—the earliest (prodromal) phase of LBD 24 . So far, only few OCT studies have prospectively evaluated the progression of retinal thinning in PD patients, 25–27 and none has specifically looked at the rate of macular GCIPL atrophy and its relationship with disease worsening.…”
mentioning
confidence: 66%
See 3 more Smart Citations
“…More recent publications have shown that the thinning of macular GCIPL in PD is linked to cognitive impairment in de novo patients 23 and to the risk of dementia 18 . Interestingly, our group found that visual dysfunction in PD is selectively associated with the thinning of GCIPL in the 1‐ to 3‐mm diameter ring area around the fovea (parafoveal GCIPL), 20 an OCT feature that has also been identified in patients with idiopathic rapid eye movement sleep behavior disorder—the earliest (prodromal) phase of LBD 24 . So far, only few OCT studies have prospectively evaluated the progression of retinal thinning in PD patients, 25–27 and none has specifically looked at the rate of macular GCIPL atrophy and its relationship with disease worsening.…”
mentioning
confidence: 66%
“…Macular and peripapillary OCT images were acquired for each eye using Spectralis spectral‐domain OCT (SD‐OCT; Heidelberg Engineering, Heidelberg, Germany), and thickness measures were calculated for peripapillary retinal nerve fiber layer (pRNFL) and for different combinations of layers and regions of the macula, as previously described 20 . Briefly, macular scans consisted of 25 single horizontal axial scans covering a 20° × 20° area (512 A‐scans per B‐scan and 49 frames per B‐scan).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In vivo neuroimaging studies in newly diagnosed and drug-naïve PD patients have detected structural alterations in the visual pathway, ranging from thinning of inner retinal layers to increased optic radiation mean diffusivity and reduced visual cortical volumes (Arrigo et al, 2017; Ahn et al, 2018; Murueta-Goyena et al, 2019), which might explain some visual disturbances. There is, however, a growing body of evidence highlighting the role of GABA in perceptual aspects of vision.…”
Section: Visual Disturbancesmentioning
confidence: 99%